The Effect of Islamic Service Ethics and Organizational Culture on Service Quality and Taxpayer Satisfaction - Aditya Halim Perdana Kusuma Putra (Golden Ratio of Taxation Studies, 2021)
This study aims to determine the effect of Islamic service ethics and organizational culture on service quality and taxpayer satisfaction at the Wajo Samsat Revenue Technical Implementation Unit office. The Islamic service ethics variable has a positive and significant effect on taxpayer satisfaction through service quality, while organizational culture has a significant negative effect on taxpayer satisfaction through service quality.